BUDAYA ORGANISASI DALAM MENINGKATKAN KINERJA GURU PADA SMA NEGERI 1 SIMEULUE TIMUR - Jurman Jurman (Jurnal Ilmiah Didaktika, 2014)
One of influencing factors in improving the teachers performance is organization culture. This study aims to know the discipline training pattern, the assumption of the importance of organization culture in improving the teachers performance and motivation, and inhibiting factors in improving the teachers performance at SMAN 1 East Simeulue of Simeulue sub-district. This study is qualitative descriptive approach. The technique of the data collection were through observations, interviews, and documentation. The subjects of the study were head master of the school, teachers, and school committee. The analysis of the research shows that (1) Fostering discipline in improving the teacher performance at SMAN 1 East Simeulue is by referring to the decided rules, whether both statutory regulations and school rules. The discipline approach was being conducted gradually started from decided job description, conducted persuasive approach, supervised the teaching-learning process, and guiding the teachers’ task, and giving impose sanctions in accordance with the offense level. (2) A system of giving motivation to the teachers in improving their performance is being conducted through giving the unbinding, good service, career promotion, training opportunities, providing services on safety and convenience of the teacher task . (3) The inhibiting factor in improving the teacher performance is the lack of the school rule socialization, lack of coordination , in effective communication amongst personnel, and lack of involvement of the school committee in deciding the school policy.